Vúsica, a música visual: um estudo da linguagem estética que revela valores e crenças dos autores surdos - Peixoto, Robson de Lima (2025)
This doctoral research, of a qualitative, exploratory, and documentary nature, adopts the perspective of the semiotics of culture and is theoretically grounded in Batista and Rastier (2015), Sutton-Spence (2021), Grasse (2023), Peixoto and Vieira (2018), and Strobel (2008). The main objective of this study was to analyze vúsicas (visual songs) in Brazilian Sign Language (Libras) created by Deaf authors and produced by and for Deaf young and adult audiences, aiming to achieve a better understanding of the values and beliefs embedded in these compositions. As a development of this overarching goal, the specific objectives were: (I) to collect vúsicas by Brazilian Deaf authors; (II) to identify recurring themes that reveal their content; and (III) to describe the aesthetic features of these compositions in Libras. The purpose of these objectives is to provide data that foster greater knowledge about this artistic manifestation — the vúsica — emphasizing its representativeness, the breaking of stereotypes, and the appreciation of Deaf culture. Among the results, 26 vúsicas authored by 12 Deaf artists were found. Based on this sample, a vusical anthology was organized, including the following information for each work: title, author, publication date, performance location, link to the vúsica video, theme, content summary, a video image excerpt, and a QR code for mobile access. In these works, the most recurring themes in songs composed by Brazilian deaf authors, their aesthetic characteristics, and the context that generated these compositions were identified. Thus, the hypothesis raised at the beginning of this study was confirmed: the main theme in most songs created in Libras (Brazilian Sign Language) for a young and adult deaf audience involves political and religious issues, as well as the ode/hymn lyrical genre. However, unlike the ode/hymn genre traditionally known in literature produced by hearing people, this way of praising/exalting the "deaf nation" does not generally occur in a solemn and formal manner. Therefore, due to this issue, we can identify that the music has similarities to the genre, but in a peculiar way within deaf culture, combined with entertainment and full of the granting of their rights.